The sales meeting - Denny, Richard; Lake, Nick; Turner, Barry; Gawith, Paul ([S.l.] : Man Management Ltd. [production company] ; Kuala Lumpur : First Training [distributor])
Explain all types of meetings especialy sales meeting. Discussed haow to handle and attend the meetings.
Camera, Mark Lipscomb ; sound supervisor, Bill Cadman ; lighting director, Nigel Fisher
Keywords: Sales meetings; Meetings; Business meetings